Genetic tendency and correlation analysis of fruit traits in the F1 population of Cuiyu × Doyenne du Comice pear - DU Chenfei; WEI Chunyan; LI Wenjue; CAI Danying; WANG Yuezhi; SHI Zebin; GAO Yongbin; DAI Meisong (Guoshu xuebao)
[Objective] This study aimed to explore the genetic tendency of important quality traits in pear fruit and the correlation between these traits, thereby enriching our understanding of the genetic laws governing pear fruit hybrid progeny. By comparing the fruit traits of parents and hybrid progenies from the cross between sand pear Cuiyu and western pear Doyenne du Comice, and conducting path analysis, we preliminarily clarified the genetic characteristics of fruit quality traits in the F1 population. This provides a theoretical basis for pear genetic breeding and QTL mapping of fruit traits. [Methods] Nine traits (single fruit weight, fruit transverse diameter, fruit longitudinal diameter, fruit stem length, fruit stem thickness, fruit hardness, soluble solids content, skin color, and fruit shape) were investigated in 136 F1 progeny individuals and both parents. Correlation analysis, multiple linear regression, and path analysis were conducted on seven traits (excluding skin color and shape) using data analysis software such as Excel and SPSS. Phenotypic data collection for fruit skin color was performed using the crop phenotype accurate identification and intelligent application platform of Zhejiang Academy of Agricultural Sciences, allowing us to explore the distribution pattern and characteristics of fruit skin color. [Results] Analysis of fruit traits in the F1 generation population and their parents (Cuiyu and Doyenne du Comice) revealed that seven quantitative traits-single fruit weight, fruit transverse diameter, fruit longitudinal diameter, fruit stem length, fruit stem thickness, flesh hardness, and soluble solids content followed a normal or partial normal distribution. The heritability of single fruit weight was 79.75%, with a separation range of 82.8-430.0 g, a coefficient of variation of 33.31%, a super-high parent rate of 12.50%, and a low parent rate of 69.85%. The heritability of fruit transverse diameter and longitudinal diameter was 82.78% and 72.68%, respectively, with separation ranges of 37.08-94.88 mm and 39.47-89.85 mm, and low parent rates of 77.94% and 78.57%, respectively. The heritability of petiole length and diameter was 99.39% and 72.90%, respectively, with the dominant rate of petiole diameter at-27.10% and a low parent rate of 73.21%. The heritability of flesh hardness was 124.35%, significantly higher than the mid-parent value, with a separation range of 4.53-35.96 N. All F1 generation fruits exhibited higher hardness than the male parent. The genetic transmissibility of soluble solids content was 83.34%, with a separation range of 5.96%-13.2% and a low parent rate of 59.52%. Correlation analysis showed that single fruit weight was significantly and positively correlated with fruit transverse diameter (r=0.944**), longitudinal diameter (r=0.858**), fruit stem thickness (r=0.262**), and soluble solids content (r=0.346**), and negatively correlated with flesh hardness (r=-0.146*). Path analysis indicated that the direct effect of fruit transverse diameter on single fruit weight was the largest (direct path coefficient=0.732), followed by fruit longitudinal diameter (0.276) and flesh hardness (0.057), while soluble solids content had the smallest effect (-0.007). The multiple regression equation (R2=0.922) further confirmed that fruit transverse diameter (X1), longitudinal diameter (X2), and fruit stem thickness (X4) were key positive predictors of single fruit quality. The inheritance of pericarp color showed incomplete dominance, with only 38.36% of offspring fruits exhibiting red halo coloring. Among these, 34.25% had small-area coloring (2%-15%), 4.11% had large-area coloring (>15%), and no fully red single plant was observed. Fruit shape inheritance was relatively stable, with 82 plants (60.29%) exhibiting the maternal round shape, 7 plants (5.15%) showing the paternal gourd shape, and 47 plants (34.56%) displaying an oblate shape. The fruit shape index was concentrated in the range of 0.85-1.00, indicating a tendency toward the maternal phenotype. In summary, the F1 progeny exhibited a low genetic tendency for most traits and a high deterioration rate. However, fruit hardness and fruit stem length showed heterosis, providing potential resources for subsequent breeding. [Conclusion] The results demonstrated that the seven important fruit traits in the Cuiyu × Doyenne du Comice F1 population-single fruit weight, fruit transverse diameter, fruit longitudinal diameter, fruit stem length, fruit stem thickness, flesh hardness, and soluble solids content were quantitative traits. Among these, fruit diameter was the key trait affecting single fruit weight. Additionally, the average values of single fruit weight, fruit transverse diameter, fruit longitudinal diameter, fruit stem thickness, and soluble solids content were lower than the mid-parent and low-parent values, with almost no heterosis observed. The genetic tendency was toward small inheritance, with obvious trait decline and a high deterioration rate. In contrast, the average values of fruit stem length and fruit hardness were higher than the low-parent value, showing strong heterosis and a higher genetic tendency. The pericarp red trait exhibited incomplete dominance, with no offspring displaying the nearly full fruit surface coloring seen in the male parent Doyenne du Comice. This suggests the presence of multiple genotypes. The genetic performance of fruit shape traits was relatively stable, with fruit shapes being round, oblate, or gourd-shaped, similar to the maternal Cuiyu or paternal Doyenne du Comice phenotypes.